Sistem Kontrol Motor Pompa Pengisi Tower Air (Tandon) - Ranu Setyobudi; Zainal Abidin; Tijaniyah Tijaniyah (Journal of Electrical Engineering and Computer (JEECOM), 2020)
The need for clean water has become a basic need that must be met every day. The community needs a lot of water consumption but sometimes a little. Due to the irregular use of water, it will result in the supply of water in the reservoir will quickly decrease which results in the volume of water in the tendon will run out.  Usually to monitor the water supply in the water storage tank (tower) using an ordinary pump, where humans fill the pump continuously or permanently. This has an impact on the reduction of water supply due to erratic usage. The author with the title "Pump Motor Control System Filling Water Tower (Tandon)" which aims if at the time of use of water expenditure is very much, the volume in the reservoir will quickly decrease. Then the pump motor will accelerate the automatic rotation so that it will quickly fill the volume of water in the reservoir. So that the tendon is not empty due to more use. And if at the time of using a small amount of water discharge, the volume in the reservoir will decrease slowly, the pump motor will automatically rotate slowly. This will be efficient and flexible due to the uncertainty of excessive usage so that the volume of water in the reservoir does not empty